EVALUASI PROGRAM MAHASISWA WIRAUSAHA UNIVERSITAS NEGERI PADANG - Hutari, Tri; Yulastri, Asmar; Yuliana, Yuliana (Ensiklopedia Sosial Review, 2020)
This research aimed to evaluate the component of context, input, process, and product on Entrepreneurship Program at Universitas Negeri Padang. This research was an evaluate study with CIPP model (Context, Input, Process, Product). The method was used a mixed method with quantitative and qualitative approach by sequential explanatory. This research was characterized by collected and analyzed quantitative data at first stage and qualitative data at second stage to reinforce the result of quantitative approach. The result of this research showed that the component of the context, input, process, and product on Entrepreneurship Program at Universitas Negeri Padang was at less satisfactory category. The component of input, process and product should be improved to make The Entrepreneurship Program to be more optimal. The recommended is The Entrepreneurship Program can proceed with the improvement at each of its components.